4. Factors Associated to Rural Households’ Demand for Financial Services in Lombok, Indonesia - I ketut Budastra (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2008)
Abstract This paper analyses factors associated with rural households’ demand for financial services in Lombok, using a survey data of 180 households randomly selected from 6 villages and 3 districts in Lombok, Indonesia. The data collection was carried out from January-June 2007. Factor associations were tested using Chi-square, Correlation and/or t-test, whichever is appropriate, depending on data measurement. It was found that the households’ demand for formal savings was significantly associated with the households’ socio-economic and banking characteristics reflecting their saving capacity (income, income sufficiency and number of earners) and preference (financial institution type, interest rate and total saving amount). The households’ demand for formal credits was also associated with their socio-economic characteristics and banking characteristics, reflecting their credit needs and preferences toward credit sources along the financial institutions’ preferences toward borrowers’ capacity to repay and risks. The faktors included: government employee possession, tertiary education possession, education, income, land assets, banking confidence, financial institution type, interest rate, credit maturity (terms), and borrower transaction costs. Abstrak Paper ini menganalisa faktor-faktor yang berasosiasi dengan permintaan ruamah tangga pedesaan terhadap layanan jasa keuangan di Lombok, menggunakan data hasil survai terhadap 180 rumah tangga yang dipilih secara acak dari 6 desa dan 3 kabupaten di Lombok yang dilakukan pada bulan Januari-Juni tahun 2007. Keberartian asosiasi antar faktor-faktor yang diteliti diuji menggunakan Chi-square, Korelasi atau t-test sesuai dengan jenis datanya. Ditemukan bahwa permintaan rumah tangga akan layanan tabungan berasosiasi dengan karakteristik sosial ekonomi dan perilaku menabung-meminjam rumah tangga pendapatan, dan jumlah pencari nafkah dalam keluarga) dan preferensi menabung mereka (jenis lembaga keuangan, tingkat bunga dan jumlah tabungan). Permintaan rumah tangga akan layanan jasa kredit juga berasosiasi dengan karakteristik sosial ekonomi dan perilaku menabung-meminjam rumah tangga yang menggambarkan kebutuhan kredit mereka dan preferensi mereka pada sumber-sumber layanan kredit bersama dengan preferensi lembaga keuangan terhadap kapasitas pengembalian kredit dan resiko kredit rumah tangga. Faktor-faktor tersebut adalah: kepemilikan anggota rumah tangga pegawai negeri, kepemilikan anggota rumah tangga berpendidikan perguruan tinggi, tingkat pendidikan kepala rumah tangga, pendapatan, aset tanah, rasa percaya diri kepala rumah tangga berurusan dengan bank, jenis lembaga keuangan, tingkat bunga, jangka waktu kredit dan biaya transaksi bagi peminjam.